Pengaruh Content Marketing Dan Brand Image Terhadap Keputusan Pembelian Produk Skincare Azarine Pada Aplikasi Tiktok (Studi Pada Mahasiswa S1 Manajemen Universitas Dharma Andalas) - Ravema Rachmi; Tiara Turay (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of content marketing and brand image on the purchase decisions of Azarine skincare products on the TikTok application, with a case study conducted among undergraduate management students at Universitas Dharma Andalas. The background of this research is based on the growing trend of social media usage, particularly TikTok, as an effective marketing medium for skincare products, as well as the importance of brand image in shaping consumer purchasing decisions. The research employed a quantitative approach with a survey method. Data were collected through questionnaires using a 5-point Likert scale. The population of this study consisted of undergraduate management students at Universitas Dharma Andalas, with a total sample of 100 respondents selected using purposive sampling techniques. Data analysis was conducted through validity and reliability tests, classical assumption tests, and multiple linear regression to test the research hypotheses. The results show that: (1) content marketing has a positive and significant effect on the purchase decisions of Azarine skincare products on TikTok, (2) brand image has a positive and significant effect on purchase decisions, and (3) content marketing and brand image simultaneously have a significant effect on purchase decisions. The coefficient of determination (R²) of 0.699 indicates that the independent variables in this study were able to explain 69.9% of the variation in purchase decisions, while the remaining 30.1% is explained by other variables outside the study. This research provides practical implications for companies to further strengthen creative and relevant content marketing strategies and to enhance a consistent brand image in order to encourage consumer purchasing decisions through social media, particularly TikTok.